Correlation between Allen cognitive level test and CANTAB in patients with Schizophrenia - Talieh Sheikh Fendereski; Hasan Ashayeri; Mitra Khalaf Beigi (Shahid Beheshti University of Medical Sciences, 2012)
Background and Aim: Schizophrenia is a severe psychiatric disorder and characterized by impairments in a wide range of cognitive domains. Allen Cognitive Level Screen has been used extensively by occupational therapists as a quick screening tool to derive a view of cognitive function in people with psychiatric disabilities. Cambridge Neuropsychological Test Automated Battery (CANTAB) is a computerized neuropsychological assessment battery which is commonly used to assess an executive functioning. The purpose of this study was to examine the relationship between two measures of executive function used by different disciplines (Allen cognitive level test and CANTAB) when assessing persons with schizophrenia. Materials and Methods: In this cross-sectional study, the relation between Allen cognitive level test`s outcome and subtests of CANTAB (SWM, SSP & IED( were investigated in 30 patients with chronic schizophrenia (Mean age= 39 , man=80%,woman=20%). Allen cognitive level test was used to measure cognitive level and Spatial Span (SSP) to measure working memory capacity, Spatial Working Memory (SWM) to evaluate working memory and its strategy of usage and Intra/Extra dimensional Set Shift (IED) to assess attentional set shifting. All the data was analyzed by SPSS-16.Results: No Significant correlation was found between cognition levels of Allen test and SWM subtest (rS= -0/046; P=0/811), SSP (rS=0/009; P= -0/024) and IED (rS= -0/074; P=0/699).Conclusion: The findings of this study suggest that although patients with schizophrenia might have problems in cognitive component, they may show less problem in performing goal directed activities. In addition, the approaches of evaluation based on which the tests have been planned should be considered for investigating the correlation between two tests. It seems that the results of a top-down approach may be different from those of a bottom-up approach.